Academic Performance as a Predictor of Success in Licensure Examinations Among Bachelor in Medical Laboratory Science Graduates - Estrada, Miriam R. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings)
Performance in the licensure examination is one of the indicators of the quality of a degree program. Academic performance shows that the graduates have met the standards of the institution. This study investigated the association between academic performance and licensure examination performance of the graduates of Bachelor in Medical Laboratory Science (BMLS). Using descriptive-evaluative and descriptive-correlational research designs and purposive sampling techniques, 335 BMLS graduates from school year (SY) 2016-2017 to 2019-2020 were included in this study, of which 102 were male, and 233 were female. For academic performance, the GPA (Grade Point Average) was used. Using the IBM SPSS Statistics version 23, data were analyzed. The results revealed that the GPA was constant at 3.5, while the board rating was highest on SY 2016-2017 and was lowest on SY 2019-2020. Overall, the lowest mean rating among the six subjects was Subject 2, with the lowest rating in SY 2018-2019 among all of the subjects. Moreover, there was a significant positive moderate relationship between academic performance and licensure performance. Results also showed that all the six subjects in the board examination were significantly correlated individually with academic performance. Using regression analysis, the Academic Performance significantly predicts Licensure Performance. This direct relationship implies that when Academic Performance is increased, board rating also increases. In this study, the GPA predicts board rating by 37.6%; therefore, 62.4% predictors remain unknown. Findings are useful in planning for the enhancement of the program and for preparation for the board licensure exam focusing on the subjects with the lowest ratings. For future research, other variables may be included to determine the other predictors of successful licensure examination performance. Keywords : License examination, academic performance, medical laboratory